2015
DOI: 10.1155/2015/858274
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Preterm Singleton Deliveries: A Population-Based Retrospective Study

Abstract: Aim. To identify sociodemographic and medical characteristics associated with preterm birth survival. Methods. A retrospective study of singleton births was performed using Missouri linked data for the years 1978 to 2005. We computed hazard ratios (HR) and 95% confidence intervals (CI) using Cox proportional hazards model. Results. High rates of infant, neonatal, and postneonatal mortality were observed among preterm as compared to term births. White are at low risk for postneonatal (HR = 0.77, CI: 0.65, 0.90)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
2
1
Order By: Relevance
“…Neonates who had RDS were one times more likely to die as compared to those who did not have RD. Consistent results have been recorded in our countries and other studies [32,34,38,45].…”
Section: Discussionsupporting
confidence: 94%
“…Neonates who had RDS were one times more likely to die as compared to those who did not have RD. Consistent results have been recorded in our countries and other studies [32,34,38,45].…”
Section: Discussionsupporting
confidence: 94%
“…This is in line with study findings in Cameroon, South Africa, South Sudan, and Mauritanian [ 42 , 43 ]. However, our finding was lower than the UNICEF national 2016 report [ 3 , 5 ] and other national reports in Africa [ 44 , 45 ], Europe, USA, and Central and West Asia [ 46 – 48 ]. This marked difference might be attributed to difference in methodology, sample size, study period, and geographic area.…”
Section: Discussioncontrasting
confidence: 87%
“…International Journal of Pediatrics than the UNICEF national 2016 report [3,5] and other national reports in Africa [44,45], Europe, USA, and Central and West Asia [46][47][48]. This marked difference might be attributed to difference in methodology, sample size, study period, and geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an increment in gestational age at birth by one week decreases the hazard of preterm neonatal deaths by 19%. This nding is in line with studies reported from the United States (12), China (21), Gonder (18), and Addis Ababa, Ethiopia (32). A possible reason for this might be as the gestational age of the neonates at birth increases, the maturity of the fetus will be enhanced, and the risk of developing life-threatening complications related to prematurity decreases and which might contribute to a reduced risk of preterm neonatal death.…”
Section: Discussionsupporting
confidence: 93%